Three very old men's experiences of mobility device use over time. (September 2013) - Kylberg, Marianne; Löfqvist, Charlotte; Phillips, Judith; Iwarsson, Susanne
Abstract: Aim: The aim of this study was to explore experiences of mobility device (MD) use among very old single-living Swedish men. Methods: A multiple case study of three men, involving quantitative and qualitative data, was used in an embedded mixed methods design and presented in three narrative stories. To capture differences and similarities in the use of MDs a cross-case analysis was conducted. Results: The findings show that the devices were important for retaining independence in everyday life and for participation in social activities. Use of MDs impacted on everyday activities by enabling, restricting, or changing the performance. Planning and careful thinking were new strategies developed for managing everyday life. The devices were purchased, received from relatives, or prescribed by professionals at a time point when there was a need. The function and form of the devices and a supportive environment were considered important for optimal use. Conclusions: These narrative stories nurture our understanding of complex and multifaceted aspects impacting on MD use in everyday life for very old men. To support active ageing, occupational therapists and other health professionals need to seek information on personal needs and expectations, in order to understand individual perspectives on MD use.